Implementasi Pendidikan Inklusi Sebagai Wujud Pembelajaran Dalam Keberagaman Di SDN Batok Bali - Nurcahyani, Nicky; Nurul Sakinah, Syafa; Tiara Aryanti, Eka; Robiansyah, Firman (JPI (Jurnal Pendidikan Inklusi), 2022)
Inclusive education is a form of education without discrimination that provides opportunities for children with special needs to obtain the same education and makes schools a comfortable place for children to receive education. This study aims to know and describe the process of implementing inclusion education and the implications of inclusion education in realizing learning in diversity in schools. The approach used is a qualitative approach with a case study method. This research was conducted at SDN Batok Bali which organizes inclusion education. Data collection techniques are carried out through observation, interviews, questionnaires, and documentation study. The results showed that the inclusion education process at SDN Batok Bali was carried out as well as the learning process in general, using the national education curriculum. It's just that students with special needs are given additional learning activities after school and there are assessment sheets given to parents to assist teachers in designing learning programs that suit student needs. The results of the questionnaire distributed to 6 respondents showed that 93% of teachers answered correctly and 7% of teachers answered incorrectly. This shows the implications of inclusive education in realizing learning in diversity at SDN Batok Bali.